Attendance and Gender Relations on Grades and Other Aspects - Andy Chung; Graham Harding; Joonhong Kim; Koot Van Wyk (International Journal of Language Teaching and Education, 2018)
Three aspects prompted this study: why are females in first year university in a countryside campus performing better than males as opposed to high school where the reverse is the case? Why are there waves of performance increases semester by semester? Why is there in the second semester always an increase in performance over the first semester? For this matter the researchers took a number of participants in total over the period 2012-2016, namely 3,963 students in Freshman English at a countryside campus (Sangju) for Kyungpook National University as their target. In the year 2016, only the first semester was calculated in this research. Three aspects were considered as far as data is concerned: attendance variables, grade variables and gender. Performances were always better in the second semester over the first and females almost always outperformed the males. What also came up as secondary considerations, are questions whether the environment like nature and the role of ‘table- talk’ of parents reverberating or not the GDP of the country over the period may have had an effect on the students. It was found when the GDP went up the students’ performance took a break but when the GDP is low the students increased their focus and performed better as their grades indicated. These last aspects were just mere observations and should be carried out with further investigation elsewhere. The attendance of females was always showing better attendance results than males for Freshmen at Sangju Campus, South Korea. While the GDP dropped and rose through the years investigated, the attendance of the students did not display a serious rise and fall but remained almost unchanged.